The potential role of RNA N6-methyladenosine in primary Sjögren’s syndrome - Xiao, Qiufeng; Wu, Xunyao; Deng, Chuiwen; Zhao, Lidan; Peng, Linyi; Zhou, Jiaxin; Zhang, Wen; Zhao, Yan; Fei, Yunyun (Frontiers in Medicine, 2022)
Objective The pathogenesis of primary Sjögren’s syndrome (pSS) remains incompletely understood. The N6-methyladenosine (m6A) RNA modification, the most abundant internal transcript modification, has close associations with multiple diseases. This study aimed to investigate the role of m6A in patients with pSS. Materials and methods This study enrolled 44 patients with pSS, 50 age- and gender-matched healthy controls (HCs), and 11 age- and gender-matched patients with non-SS sicca. We detected the messenger RNA (mRNA) levels of m6A elements (including METTL3, WTAP, RBM15, ALKBH5, FTO, YTHDF1, YTHDF2, YTHDF3, YTHDC1, and YTHDC2), ISG15, and USP18 in peripheral blood mononuclear cells (PBMCs) from patients with pSS, patients with non-SS sicca, and HCs. The clinical characteristics and laboratory findings of patients with pSS and patients with non-SS sicca were also collected. We used binary logistic regression to determine if m6A elements were risk factors for pSS. Results The mRNA levels of m6A writers (METTL3 and RBM15), erasers (ALKBH5 and FTO), and readers (YTHDF1, YTHDF2, YTHDF3, YTHDC1, and YTHDC2) were all significantly higher in PBMCs from patients with pSS than in HCs. The mRNA levels of m6A writers (METTL3 and WTAP) and readers (YTHDF2, YTHDF3, and YTHDC2) were lower in PBMCs from patients with pSS compared to patients with non-SS sicca. The expression of METTL3, RBM15, FTO, YTHDF1, YTHDF2, YTHDC1, and YTHDC2 was positively correlated with the level of C-reactive protein (CRP) of patients with pSS. The mRNA level of YTHDF1 in PBMCs from patients with pSS was negatively correlated with the EULAR Sjögren’s syndrome disease activity index (ESSDAI) score. In patients with pSS, FTO, YTHDC1, and YTHDC2 were also related to white blood cells (WBCs), neutrophils, lymphocytes, and monocytes. Increased mRNA level of ALKBH5 in PBMCs was a risk factor for pSS, as determined by binary logistic regression analysis. The mRNA level of ISG15 was positively correlated with that of FTO, YTHDF2, YTHDF3, and YTHDC2 in patients with pSS. Conclusion Compared with HCs, the expression of METTL3, RBM15, ALKBH5, FTO, YTHDF1, YTHDF2, YTHDF3, YTHDC1, and YTHDC2 was considerably higher in PBMCs from patients with pSS. In comparison with patients with non-SS sicca, the expression of METTL3, WTAP, YTHDF2, YTHDF3, and YTHDC2 was reduced in PBMCs from patients with pSS. The m6A elements correlating with clinical variables may indicate the disease activity and inflammation status of pSS. Elevated expression of ALKBH5 was a risk factor for pSS. The dynamic process of m6A modification is active in pSS. m6A elements (FTO, YTHDF2, YTHDF3, or YTHDC2) might target ISG15, stimulate the expression of ISG15, and activate the type I IFN signaling pathway, playing an active role in initiating the autoimmunity in pSS.